FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN KUNJUNGAN ULANG IBU BALITA LAKI – LAKI PNEUMONIA DI KELURAHAN TANDANG SEMARANG - Anggrainy, Yeny; Widagdo, Laksmono; Istiarti, VG Tinuk (Jurnal Kesehatan Masyarakat (e-Journal), 2017)
Pneumonia in Semarang city was in the 2nd rank in 2016 with 5542 cases, and Kedungmundu Health Center had the highest peneumonia patients which were 509 toddlers male and female. One of the most important management in pneumonia is on the second day when parents and toddlers are required to make a return visit. Return visit is needed to prevent pneumonia severity on toddlers and if not done, will affect on health particularly the increasing case of pneumonia from mild pneumonia to severe pneumonia. Return visit’s coverage in Kedungmundu Health Center was still low which was only 13% from the total of 509 toddlers male and female patients.  The aim of this research was to analyzed factors related to the compliance of return visit in mother of toddlers’s male with pneumonia in Tandang District.This research was a analytical descriptive research with cross sectional approach. Sampling techinique was using total population of the mothers who have toddler’s male with pneumonia in Tandang District. Data was collected using questionnaire. The results showed that most of the respondents were 26-35 years old, have graduated from high school, were housewives and have low income <UMR (Rp 2,125,000). 84.4% of respondents did not do pneumonia’s return visit. The chi-square test showed that age (p=0,046), knowledge of pneumonia and pneumonia’s re-visit (p=0,029), and motivation (p=0,023) were correlate with the compliance of pneumonia’s re-visit. Meanwhile, educational level (p=0,438), occupation (p=0,485), revenue (0,438), attitudes (p=0,063), ease of access (p=0,187), family support (p=0,311), and support of health workers  (p=0,124) were not correlate with the compliance of pneumonia’s re-visit. This research recommended optimization of counseling to mothers of pneumonia’s toddler about the importance of pneumonia’s return visit, especially for toddlers whose condition have improved should keep visiting the health center.